Linking Mitochondrial Function to Insulin Resistance: Focusing on Comparing the Old and the Young - Wang, Jingxuan; Wu, Junnan; Li, Wenjing; Wang, Xinyu; Liu, Ruifang; Liu, Tao; Xiao, Jianhua (Frontiers in Nutrition, 2022)
Long-term intake of high-energy diet can lead to decreased insulin sensitivity and even insulin resistance, eventually leading to diabetes. Diabetes often occurs in middle-aged and elderly people. However, there is growing evidence that the incidence rate of young body is increasing over the years. This means that insulin resistance can be caused by excessive energy intake in both young and old people. In this study, high-fat diet (HFD) and normal diet were fed to rats of elderly experimental group (EE), elderly control group (EC), young experimental group (YE), and young control group (YC), respectively, for 8 weeks, by which insulin resistance model was obtained. Insulin sensitivity was measured, histopathology changes in liver and skeletal muscle tissues were observed, and mitochondrial fusion and division and cell senescence were detected in four groups of rats. The results showed that both young and elderly rats developed significant insulin resistance, fat deposition, decline of mitochondrial function and mitochondrial biosynthesis in liver and skeletal muscle, and cell aging after HFD feeding. In addition, the degree of mitochondrial dysfunction and aging in young rats was similar to that of aged rats fed a normal diet after HFD. This experiment provides a reference for an in-depth study of the regulatory mechanisms of cellular energy metabolism in this state.